2020
DOI: 10.1002/pro.3860
|View full text |Cite
|
Sign up to set email alerts
|

Cellular functions and intrinsic attributes of the ATP‐binding Eps15 homology domain‐containing proteins

Abstract: Several cellular processes rely on a cohort of dedicated proteins that manage tubulation, fission, and fusion of membranes. A notably large number of them belong to the dynamin superfamily of proteins. Among them is the evolutionarily conserved group of ATP-binding Eps15-homology domain-containing proteins (EHDs). In the two decades since their discovery, EHDs have been linked to a range of cellular processes that require remodeling or maintenance of specific membrane shapes such as during endocytic recycling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…In mammals, four EHD orthologs are found (EHD1-4) that show distinct tissue-specific expression, localization, and functions (Pohl et al, 2000 ; George et al, 2007 ). EHD1, 3 and 4 are observed at early and late endosomes and EHD2 is located primarily at the caveolar neck (reviewed in Naslavsky and Caplan, 2011 ; Bhattacharyya and Pucadyil, 2020 ). All EHD proteins are able to bind to and bend phospholipid membranes (Daumke et al, 2007 ; Melo et al, 2017 ; Deo et al, 2018 ).…”
Section: Atp Dependent Ehd2 Oligomerization At the Caveolar Neckmentioning
confidence: 99%
“…In mammals, four EHD orthologs are found (EHD1-4) that show distinct tissue-specific expression, localization, and functions (Pohl et al, 2000 ; George et al, 2007 ). EHD1, 3 and 4 are observed at early and late endosomes and EHD2 is located primarily at the caveolar neck (reviewed in Naslavsky and Caplan, 2011 ; Bhattacharyya and Pucadyil, 2020 ). All EHD proteins are able to bind to and bend phospholipid membranes (Daumke et al, 2007 ; Melo et al, 2017 ; Deo et al, 2018 ).…”
Section: Atp Dependent Ehd2 Oligomerization At the Caveolar Neckmentioning
confidence: 99%
“…Prevailing mechanistic models for EHD proteins like RME-1 deviate from the canonical, mechanochemical model for the neuronal dynamin-1. 12,36 Beyond the preference for ATP (not GTP) and very slow hydrolysis rates, EHD proteins (and non-neuronal dynamin-2 37 ;) appear to work with N-BAR protein partners on elongated tubules. 8,14,15,38 As reported previously, 23 we show that the EHD homolog, RME-1, causes membrane tubulation, but does not exhibit membrane fission activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous work indicated that tubules formed with RME-1 and AMPH-1 are significantly shorter than those formed by either protein alone. 8 Although the role for EHD proteins appears disparate, 12,36 there is some evidence linking ATP hydrolysis and membrane fission for the closest RME-1 homolog in humans, EHD-1. 39 Furthermore, rme-1 mutants in C. elegans (and loss of EHD-1 in mammalian cells) block receptor release from enlarged recycling endosomes, suggesting a positive role in carrier formation, and mutations that disrupt the interaction between RME-1 and AMPH-1 are likewise defective in recycling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, due to the presence of long unstructured linkers regions between well-folded domains of scaffold proteins, the effective curvature can be thought to have a distribution rather than a fixed value 135,136 . Scaffold proteins such as Amphiphysin1 from the BAR family 119 , Epsin N-terminal homology domain 137 , dynamic and EHD proteins 47,111,138,139 and AP180 137…”
Section: Curvature Calculationmentioning
confidence: 99%